PERFORMANCE APPRAISAL PRACTICES IN 21 ST CENTURY: CONCERNS AND CHALLENGES - Sujith A. S. (MIRROR, 2018)
Performance Appraisal has been considered as the most significant an indispensable tool for an organization, for an organization, for the information it provides is highly useful in making decisions regarding various personnel aspects such as promotion and merit increases. Performance measures also link information gathering and decision making processes which provide a basis for judging the effectiveness of personnel sub-divisions such as recruiting, selection, training and compensation. In every organisation, employees play a vital role in determining its survival. Employees become the ultimate asset to ensure that the organization operates as planned. The relation between the appraisal system and the organisation’s strategy is used as a strategic tool to achieve the organisation’s vision. This will evidently be a key factor in communicating values, promoting flexibility and maximizing individual potentials and contributions. Very often, employees who are not happy with the practice of the appraisal activities will send a huge impact on the organization’s image. In the 21st century, performance appraisal activities continue to become one of the most important functions in human resource management. The work environment and the employees have become more in tune because of the massive usage of information and communication technology (ICT) in every organisation. This paper explains the relationship of the 21st century with performance appraisal activities and explores issues as well as challenges that arise in the appraisal activities.